Harnessing immunotherapy: cancer vaccines as novel therapeutic strategies for brain tumor - Kiel, Klaudia; Piranlioglu, Raziye; Godlewski, Jakub; Bronisz, Agnieszka (Frontiers in Immunology, 2025)
Cancer vaccines have emerged as a pivotal area of research in oncology, demonstrating significant promise in harnessing the immune system to combat cancer. Recent advancements in antigen identification and sequencing techniques have catalyzed the development of cancer vaccines whose goal is to elicit robust humoral and cellular immune responses against cancer cells. Despite their potential, most cancer vaccines are still in the experimental phase, primarily due to challenges associated with tumor-induced immune suppression. This article explores the role of cancer vaccines in brain cancer, glioblastoma, by providing a granular analysis of clinical trial results and mechanisms of resistance alongside a comparative assessment. These vaccines aim to navigate the immunosuppressive tumor microenvironment by targeting glioblastoma-specific antigens, offering new hope for improved treatment outcomes. The unique mechanisms defining cancer vaccines, such as their ability to activate dendritic cells and T cells, underscore their precision in selectively attacking cancer cells while sparing healthy tissue. Furthermore, the categorization of these vaccines into preventive and therapeutic types, along with various delivery methods, illustrates their diverse capacity. Finally, this review highlights the potential impact of cancer vaccine clinical trials on future cancer therapies, where effective anti-cancer strategies are within reach. It also provides an in-depth discussion of the brain tumor microenvironment and its influence on vaccine efficacy.